Selenium Transport Mechanism via Selenoprotein P—Its Physiological Role and Related Diseases - Saito, Yoshiro (Frontiers in Nutrition, 2021)
Selenoprotein P (SELENOP) is selenium (Se)-containing protein in plasma, which is primarily produced in the liver. The “P” in SELENOP is originated from the presence in plasma. SELENOP contains selenocysteine, a cysteine analog containing Se instead of sulfur. SELENOP is a multi-functional protein to reduce phospholipid hydroperoxides and to deliver Se from the liver to other tissues, such as the brain and testis, playing a pivotal role in Se metabolism and antioxidative defense. A decrease of SELENOP causes various dysfunctions related to Se deficiency and oxidative stress, while excess SELENOP causes insulin resistance. This review focuses on the Se transport system of SELENOP, particularly its molecular mechanism and physiological role in Se metabolism. Furthermore, the chemical form of Se and its biological meaning is discussed.